Nosilnost lameliranih lepljenih nosilcev iz bukovega lesa - Fortuna, Barbara (Gradbeni vestnik, 2023)
The article presents the results of an experimental investigation of the mechanical properties of glued laminated beech beams. Two groups of beams were made from longitudinally glued beech boards with two different finger joint geometries. Before the production of the two series of glued laminated beams, different finger joint profiles were analysed. Three different types of structural adhesives were used. The results of the experimental testing confirmed the results of the numerical analysis and it was found that longer and sharper finger joints allow higher tensile strengths of finger joints on beech wood. The type of adhesive has no significant influence on the strengths. Higher tensile strengths of finger joints have a direct influence on higher bending strengths of glued laminated beams. The experimental bending tests confirmed that longer finger joints with higher mechanical properties have a significant influence on the bending strength of the glued laminated beams.
Keywords: beech wood; bukov les; finger joints; glued laminated beams; lamelirani lepljeni nosilci; natezni in upogibni test; tensile and bending tests; zobati spoji